Push-Up Technique and Anatomical Deployment With the Endurant Stent-Graft System for Severely Angulated Aneurysm Necks. (June 2017) - Dohi, Shizuyuki; Yokoyama, Yasutaka; Yamamoto, Taira; Kuwaki, Kenji; Hariya, Akifusa; Kajimoto, Kan; Yamaoka, Hironobu; Shimada, Akie; Tsuruta, Ryo; Amano, Atsushi
Purpose: To describe a technique suitable for treating severely angulated (>75°) necks during endovascular aneurysm repair using the Endurant stent-graft.Technique: In the push-up technique, the suprarenal stent is released early to fix the proximal stent-graft in place so that each stent in the neck can be deployed individually without displacing the device upward. It is important to push the delivery system up after each stent deployment to allow the fabric between the stents to fold up circumferentially. By doing so, there is minimal upward force applied to the suprarenal stent. Because the stents expand along the angulated neck while catching blood flow, this anatomical deployment is feasible, with hardly any change to the proximal neck shape after stent-graft implantation.Conclusion: The push-up technique and anatomical deployment with the Endurant stent-graft system are effective and safe methods for treating aneurysms with severely angulated necks.